Malaysia : Selected Issues. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2015)
This Selected Issues paper examines the implications of lower crude oil prices on Malaysia's economy. Although Malaysia's net oil exports are now very small as a share of GDP, its gas exports are sizeable. The paper provides some background on the structure of energy production and trade in Malaysia, and presents results from empirical analysis of the oil prices on Malaysia's growth. It is concluded that the decline in prices is likely to have a net negative impact on growth, even though the recent decline in oil prices partially reflects supply considerations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Public Administration; Public Sector Accounting and Audits